The Impact of Daxi High-Speed Railway on Shanxi’s Economic Development - Xue, Fang; Bednář, Milan, 1991-; Pavlíček, Tomáš; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2022)
This diploma thesis focuses on the impact of the Daxi High-Speed Railway on the accessibility, economic development, and industrial structure of the Shanxi Province. In the theoretical part, the technical and economic characteristic of the high-speed railway was analyzed. The high-speed railway causes a crowding out effect on other transportation modes since it is more competitive and offers a more secure way of transportation, larger capacity, and punctuality. In addition, the theories of transportation economy and the regional economic theories are introduced to show the importance of transportation in regional economic development. In the analytical part, the accessibility evaluation model was presented to show that the accessibility of the Shanxi Province increased after the opening of Daxi HSR. However, the improvement of the accessibility differed among the cities depending on their geographical location, economic status, and interaction with other cities. The result of the difference-in-differences method shows that the opening of the Daxi HSR has a significant positive effect on the GDP growth rate, GDP per capita, and the industrial upgrading index in Shanxi. The Siphon effect means the potential that a high-speed railway may transfer production factors along the route to developed regions, which brings negative effects to less developed regions. As a final perspective, the principal component analysis was conducted to show the diverse impact of regional economies along the railway, which demonstrates the siphon effect.
Vedoucí práce: Milan Bednář
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: economics and public policy [obor dipl. práce]; diplomové práce; master's theses